A test of hand separators - McCrone, Edwin William (My University, 1903)
Introduction: Within recent years there has been invented a machine which has revolutionized the dairy business. This machine is the hand centrifugal separator. The first machines were comparatively simple affairs, the essential feature of which was a cylindrical bowl, which by means of a suitable mechanism was given a rotary motion with great speed. The milk was fed into the top of the bowl and came out at openings made for the purpose. This simple machine had a great advantage over the old system of gravity setting. It was but a short time however after the original machine was invented, until others went to work to make improvements, which resulted in several new and better machines. To -day we have six different machines which are sold quite largely in the west and there is intense rivalry among the manufacturers. The manufacturers of these machines advertise extensively and each manufacturer claims to have the machine which will skim the closest, run the easiest, and last the longest. All of this is very confusing to the prospective purchasers many of whom have never run a separator and have no basis on which to form an opinion of the merits of a machine. In order to in some measure overcome these difficulties an experiment was undertaken to test the respective merits of six of the machines in most common use, namely: DeLaval, Sharpless, Empire, Iowa Dairy, National, and United States. While this test is in many ways not all that could be wished for it is hoped that it may at least be a help to any one wishing to select a separator. It is incomplete in that it was made with but one machine of each kind and that it was not continued as long as could be desired. However we have made tests under some of the more common adverse conditions likely to be encountered on the farm or dairy. It is hoped also that the care and accuracy with which it has been conducted may in some small degree compensate for the incompleteness which characterizes some of its parts.
Citation: McCrone, Edwin William. A test of hand separators. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Dairy Equipment; Cream Separator; Comparison; Theses